Ontologi Filsafat Pancasila Di Desa Perdamaian Kecamatan Tanjung Morawa Kabupaten Deli Serdang - Linton Naibaho, Rahma Dhani Fitria Sinaga, Wulan Ayu Trisna (Jurnal Pusat Studi Pendidikan Rakyat, 2023)
This study aims to understand the ontology of Pancasila Philosophy in Perdamean Village, Tanjung Morawa District, Deli Serdang Regency. Ontologically, the investigation of Pancasila as a philosophy is intended as an attempt to find out the basic nature of the Pancasila precepts.The problem is focused on the lack of application of Pancasila by some audiences in social life. In this research the author uses a qualitative descriptive method to clarify a description, conditions, or things by describing them in as much detail as possible based on the facts There is. The results of the research show that the ontology of Pancasila philosophy in the village of Peace is quite good, but there are some people who are still apathetic about the application of Pancasila in their lives, therefore there is a need for an approach by the family and village government.